D-D dimer levels in patients with sickle cell disease during bone pain crises and in the steady state - Fakunle EE; Eteng KI; Shokunbi WA (Dove Medical Press, 2012)
Eyitayo Emmanuel Fakunle,1 Kapoona Iwara Ibiang Eteng,2 Wuraola Adebola Shokunbi21Department of Pathology, King Edward VII Memorial Hospital, Bermuda; 2Department of Hematology, University College Hospital, Ibadan, NigeriaObjective: To determine the presence of ongoing thrombosis by measuring the D-D dimer levels in bone pain crises (BPCs) and in the steady state of patients with sickle cell disease, comparing these levels with those in individuals with normal hemoglobin (HbAA) in southwest Nigeria.Study design, patients, and methods: The study design involved 38 patients with homozygous sickle cell anemia (HbSS) and 78 adults with the HbAA phenotype, seen at the Hematology Day Care and Accident and Emergency units of the University College Hospital, Ibadan, Nigeria. The TintElize kit was used to quantitatively determine human D-D dimer levels in the plasma with enzyme immunoassay.Results: The mean D-D dimer level measured of the 78 individuals with HbAA was 73.59 ng/mL. The mean D-D dimer level of the patients with HbSS during BPCs was 4002.40 ng/mL, while the mean level in the same patients in the steady state measured 6 weeks after their BPCs, with no other painful crisis episode before the sample was collected, was 1320.00 ng/mL.Conclusion: This study demonstrated a significant increase in the D-D dimer levels of patients with HbSS in the steady state, when compared with those of individuals with HbAA of the same age and sex distribution. There was also an approximate threefold increase in the D-D dimer levels in the same patients with HbSS during BPCs. This confirms the activation of coagulation and fibrinolytic systems in patients with HbSS in the steady state, which is further escalated during BPCs. A multicenter study on the use of anticoagulants in BPCs in patients with sickle cell disease is required.Keywords: anticoagulant, dimer, sickle cell disease, BPC, Nigeria, chronic hemolytic anemia